ANALISIS KAUSALITAS DAN KOINTEGRASI FOREIGN DIRECT INVESTMENT (FDI) TERHADAP PERTUMBUHAN GROSS DOMESTIC PRODUCT (GDP) ASEAN-5 - Rais, Irfan Maulana; Mahaendra Yasa, I Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009]DO - 10.24843/EEP.2022.v11.i10.p12, 2022)
The purpose of this study is to analyze the causal relationship (causality) of foreign direct investment (FDI) to gross domestic product (GDP) growth in ASEAN-5 and to determine the long-term relationship (cointegration) of foreign direct investment to gross domestic product growth in ASEAN. ASEAN-5. This research uses a quantitative approach in the form of causal associative conducted in ASEAN-5, namely Indonesia, Malaysia, Singapore, Thailand and the Philippines. The types of data used are quantitative data and qualitative data, and the data sources used are secondary data from the World Bank over a period of thirteen years, namely, the 2007-2019 period in countries that are members of ASEAN-5. The data collection method used is non-participant observation. The analysis technique used is pedroni cointegration test and Granger causality. The results of the analysis in this study indicate that there is a one-way relationship between Foreign Direct Investment (FDI) and Gross Domestic Product (GDP) growth in ASEAN-5, and there is a long-term relationship between Foreign Direct Investment (FDI) and Gross Domestic Product growth (GDP) in ASEAN-5.